Retorika Kepentingan Nasional dalam Pidato Diplomatik Indonesia di Forum PBB: Analisis Wacana Kritis - Galuh Ratnatika; Didik Setiawan; Edison Bonar Tua Hutapea (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
This study examines the rhetorical strategies of national interest representation employed by Indonesia in its diplomatic speeches at the United Nations General Assembly (UNGA) from 2019 to 2024. Diplomatic speeches at global forums are not merely policy-position statements. They constitute discursive practices that construct identity, legitimacy, and power hierarchies among international actors. This study applies Norman Fairclough's Critical Discourse Analysis (CDA) framework covering three analytical dimensions: text, discursive practice, and social practice. Five official speeches delivered by President Joko Widodo (2019-2023) and President Prabowo Subianto (2024) at the UNGA were analyzed. The findings reveal three dominant and recurring rhetorical strategies. First, positioning Indonesia as a responsible middle power through metaphors of peace and multilateralism. Second, constructing a collective Global South identity to legitimize domestic economic interests. Third, employing international morality rhetoric to frame pragmatic foreign policy interests. This study argues that Indonesia's diplomatic speeches at the UN function not only as inter-state communication but also as arenas for image construction and national interest negotiation through language.